GRATITUDE AS THE FOUNDATION OF ISLAMIC EDUCATIONAL VALUES (STUDY OF THE QUR'AN SURAT AL-FATIHAH) - Aslihah, Aslihah; Wasehudin, Wasehudin (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2023)
The implementation of education in Indonesia is none other than to produce a golden generation that is intelligent and has noble character. Intelligence possessed not only in the academic field, but must be spiritually intelligent. The current moral degradation is caused by many triggering factors. The most visible factor is the increasing sophistication of information and communication technology which has not been utilized properly by the community and youth, and the association of adolescents that is too free so that spiritual intelligence has not been formed. Spiritual intelligence needs to be instilled from an early age, one of which is by forming gratitude as the foundation of educational values. Gratitude needs to be trained for every human being under any circumstances, because gratitude is not only spoken but must be manifested by concrete actions. This research is a library research or library research, in this case the researcher looks for sources and data from books, journals, and commentary books that are in accordance with the research title. This is in accordance with the content of QS Al-Fatihah related to the educational values in it. The results of this study include the value of aqidah (tauhid) education, sharia education, religious education, moral education and historical education.